Pengaruh Infusa Rimpang Temu Putih (Curcuma zedoaria (Berg.) Roscoe) Terhadap Jumlah Leukosit Dan Differential Counting (Diffcount) Pada Kesembuhan Luka Laparatomi Pasca Bedah: Effect of Infusion of Temu Putih Rhizome (Curcuma zedoaria (Berg.) Roscoe) on Leukocyte Count and Differential Counting (Diffcount) on Postoperative Laparotomy Wound Healing - Wulandari, Ratna; Puspitasari, Puspitasari (Universitas Muhammadiyah Sidoarjo, 2019)
Laparatomy is surgery performed to open the abdominal area which causes an increase in plasma adrenaline and inflammatory. Leukocytes will increase if the adrenal glands are stimulated as a physiological response such as stress and when active against microorganisms. Leukocytosis can trigger an increase in the number of neutrophil and lymphocyte cells in the blood circulation and cause an increase in leukocytes and diffcount. Curcuma zedoaria contain curcumin compounds as antioxidant effectiveness to prevent fisiologis stress, flavonoid and essential oils as an anti-inflammatory which can increase the total of leukocyte. The objective of this research is to determine the effect of several Curcuma zedoaria infusion on the total of leukocytes and diffcount on post operative laparatomy wound healing. A total of 24 Rattus norvegicus were used in this research. Group I (without infusion); group II (10% infusion); group III (15% infusion); group IV (20% infusion). Rattus norvegicus were sreened laparatomy and their blood was taken for leukocyte and differential counting. There is an effect of Curcuma zedoaria infusion on the number of leukocytes and diffcount. The best concentration 15% of leukocyte, and diffcount such as concentration 20% granulocyte, concentration 15% lymphocytes and concentration 10% monocyte in postoperative laparatomy wound healing.